Judicial Independence in the Enforcement of Military Crimes in the Indonesian Justice System - Joko Sasmito (APPTHI, 2018)
The military court has the function of carrying out judicial duties in the context of upholding law and justice by taking into account the interests of the administration of state defense and security, which in this case, is carried out by the military. However, it should be remembered that law enforcement through military courts is the last resort (ultimum remidium) when disciplinary law enforcement by superiors fails to overcome the existing problems. Military Courts are regulated in Article 10 of Law No. 31 of 1997, that Courts under Military Courts are authorized to try crimes committed in the jurisdiction of defendants, including units in their jurisdiction. The protection of judicial independence is usually considered to cover various aspects that operate at different levels, in this case, external and internal independence and institutional and individual independence. External independence refers to the independence of the judiciary from political branches (Executive and Legislative powers), as well as other non-judicial actors. However, there must be a relationship between the judiciary and political power (especially the executive). The importance of the independence, impartiality, and competence of military courts is recognized by all experts. In a number of presentations, it was noted that, in some countries, the issue of command interference and lack of institutional independence remains a source of concern. Regarding the personal jurisdiction of military courts, the Human Rights Committee has discussed this issue, stating that civilians should not submit to the jurisdiction of military courts except in exceptional circumstances. Military jurisdiction should be set aside in favor of civilian courts in cases where allegations of serious human rights violations are made against military personnel, and that military jurisdiction should be limited to military offenses. Abstrak Peradilan militer mempunyai fungsi melaksanakan tugas peradilan dalam rangka penegakan hukum dan keadilan dengan memperhatikan kepentingan penyelenggaraan pertahanan dan keamanan negara, yang dalam hal ini dilakukan oleh militer. Namun perlu diingat bahwa penegakan hukum melalui peradilan militer merupakan upaya terakhir (ultimum remidium) ketika penegakan hukum disiplin oleh atasan gagal mengatasi permasalahan yang ada. Peradilan Militer diatur dalam Pasal 10 Undang-Undang No. 31 Tahun 1997, bahwa Pengadilan di lingkungan Peradilan Militer berwenang untuk mengadili kejahatan yang dilakukan dalam wilayah hukum atau para terdakwa, termasuk unit-unit yang berada dalam wilayah hukumnya. Perlindungan independensi peradilan biasanya dianggap mencakup berbagai aspek yang beroperasi pada berbagai tingkatan, dalam hal ini independensi eksternal dan internal, serta independensi institusional dan individu. Independensi eksternal mengacu pada independensi peradilan dari cabang-cabang politik (kekuasaan eksekutif dan legislatif), serta aktor non-yudisial lainnya, meskipun harus ada hubungan antara kekuasaan yudikatif dan politik (khususnya eksekutif). Pentingnya kemandirian, ketidakberpihakan dan kompetensi pengadilan militer diakui oleh semua ahli. Dalam sejumlah presentasi, disebutkan bahwa di beberapa negara, isu campur tangan komando dan kurangnya independensi kelembagaan masih menjadi perhatian. Mengenai yurisdiksi pribadi pengadilan militer, Komite Hak Asasi Manusia telah membahas masalah ini yang menyatakan bahwa warga sipil tidak boleh tunduk pada yurisdiksi pengadilan militer kecuali dalam keadaan luar biasa. Yurisdiksi militer harus dikesampingkan demi pengadilan sipil dalam kasus-kasus di mana tuduhan pelanggaran hak asasi manusia yang serius dilakukan terhadap personel militer dan bahwa yurisdiksi militer harus dibatasi pada pelanggaran militer. Kata kunci: Kemerdekaan, Hakim, Kejahatan, Sistem Peradilan, Militer, Indonesia